Targeting Interleukin-1β Reduces Leukocyte Production After Acute Myocardial Infarction. Issue 20 (17th November 2015) - Sager, Hendrik B.; Heidt, Timo; Hulsmans, Maarten; Dutta, Partha; Courties, Gabriel; Sebas, Matthew; Wojtkiewicz, Gregory R.; Tricot, Benoit; Iwamoto, Yoshiko; Sun, Yuan; Weissleder, Ralph; Libby, Peter; et al.
Abstract : Background—: Myocardial infarction (MI) is an ischemic wound that recruits millions of leukocytes. MI-associated blood leukocytosis correlates inversely with patient survival, yet the signals driving heightened leukocyte production after MI remain incompletely understood. Methods and Results—: With the use of parabiosis surgery, this study shows that soluble danger signals, among them interleukin-1β, increase bone marrow hematopoietic stem cell proliferation after MI. Data obtained in bone marrow reconstitution experiments reveal that interleukin-1β enhances hematopoietic stem cell proliferation by both direct actions on hematopoietic cells and through modulation of the bone marrow's hematopoietic microenvironment. An antibody that neutralizes interleukin-1β suppresses these effects. Anti-interleukin-1β treatment dampens the post-MI increase in hematopoietic stem cell proliferation. Consequently, decreased leukocyte numbers in the blood and infarct reduce inflammation and diminish post-MI heart failure in ApoE –/– mice with atherosclerosis. Conclusions—: The presented insight into post-MI bone marrow activation identifies a mechanistic target for muting inflammation in the ischemically damaged heart. Abstract : Supplemental Digital Content is available in the text.